Kritik Sanad Hadis (Studi Sunan Ibnu Majah, Kitab Az-Zuhud) - Arifin, Zainal (Hikmah Journal of Islamic Studies, 2018)
There are three elements of the validity of the method in determining the authenticity of a Hadith: it’s connection by isnad, credibility of the narrator, syużūż and ‘illah. The focus of the study in this article is to examine the isnad hadith narrated by Ibn Majah through companions ‘Abd ar-Rahman (Abu Hurayrah) found in Sunan Ibn Majah, Kitab al-Zuhud, hadith number 4102. it’s done by takhreej of hadith and i’tibar, it recorded by researchers the quality of the narrators and its connectioned, and the possibility of checking by syużūż and ‘illah. Finally seen that entire hadith is created by śiqat and its isnaad muttaşil (connected) from the Prophet Muhammad to the last creature and Ibn Majah as mukharrij al-hadith, and not found the presence of syużūż or ‘illah, so that have the best quality that can enter the category of hadith is hasan li ghairih. Keywords: Isnad Criticism, Hadith, Kitab al-Zuhud Terdapat tiga unsur kaedah kesahihan dalam menentukan keotentikan suatu hadis, yaitu ketersambungan sanad, kredibilitas rawi, serta syużūż (kejanggalan), dan ‘illah (kecacatan). Fokus kajian dalam artikel ini adalah meneliti sanad hadis yang diriwayatkan oleh Ibnu Majah melalui sahabat ‘Abd ar-Rahman (Abu Hurairah) yang terdapat pada Sunan Ibnu Majah, Kitab al-Zuhud, nomor hadis 4102. Yakni dengan dilakukan takhrij hadis dan i’tibar, diteliti kualitas perawi dan ketersambungan sanadnya, dan dilakukuan pengecekan kemungkinan adanya syużūż dan ‘illah. Akhirnya terlihat bahwa seluruh periwayat hadis tersebut bersifat śiqat dan sanadnya muttaşil (tersambung) dari Nabi Muhammad SAW sampai kepada periwayat terakhir Ibnu Majah yang sekaligus sebagai mukharrij al-hadis, dan tidak ditemukan adanya syużūż (kejanggalan) ataupun ‘illah (cacat), sehingga kwalitasnya bisa masuk kategori hadis hasan li ghairih. Kata Kunci: Kritik sanad, Hadis, Kitab al-Zuhud